2011
DOI: 10.4103/0976-237x.91794
|View full text |Cite
|
Sign up to set email alerts
|

Work-related musculoskeletal disorders among dental surgeons: A pilot study

Abstract: Aim:To describe the work-related musculoskeletal disorders among on-job dental surgeons.Objectives:To identify the musculoskeletal disorders in terms of perception of pain and stiffness experienced by the dental surgeons due to the rigors of dental work, to determine the prevailing working environment with particular reference to dental work station in relation to musculoskeletal disorders, and to find the association between pain and stiffness experienced by the dental surgeons and the selected socio-demograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 8 publications
3
25
0
3
Order By: Relevance
“…15 Coinciding with these studies, the current study found that there was statistically significant association (χ2 =8.58, p = 0.014) between the frequency of stiffness and age.…”
Section: Discussionsupporting
confidence: 79%
“…15 Coinciding with these studies, the current study found that there was statistically significant association (χ2 =8.58, p = 0.014) between the frequency of stiffness and age.…”
Section: Discussionsupporting
confidence: 79%
“…3 The Occupational disorders have not only effects psychological, physical and social consequences, but also effects the security impact and economic they reach level of severity that affects work capacity and decreased quality of life. 4 There are various socioeconomic factors like lack of education, poverty, excess workings hours, poor diet and poor working conditions that effect health illness. 5 The WMSDs primarily caused by repetitive movements, poor posture, continuous static work, heavy physical work, frequent bending twisting, whole body vibration, manual handling and improper ergonomic.…”
Section: Introductionmentioning
confidence: 99%
“…Vale ressaltar que as cargas de trabalho impostas aos CDs, o desconforto físico, um posto de trabalho mal projetado sob o ponto de vista ergonômico e a má postura são fatores determinantes para o surgimento de doenças de origem ocupacional nesses profissionais, incomodando, e, algumas vezes, até incapacitando o seu desempenho profissional 1,3,4,32 .…”
Section: Discussionunclassified
“…A literatura sobre a relação entre tarefas repetitivas e monótonas com comprometimento da saúde dos trabalhadores é vasta, principalmente porque são fatores de risco para o desenvolvimento de doenças ocupacionais. Logo, os resultados obtidos neste estudo mostram congruência com evidências apontadas nos demais [1][2][3][4][5][6] .…”
Section: Tabela 4 Pontuação Do íNdice De Capacidade Para O Trabalho (unclassified
See 1 more Smart Citation